2020
DOI: 10.1088/1755-1315/478/1/012068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Bovine Serum Albumin (BSA) Levels on the Sperm Viability of Ongole Cross Bred Bull during 5°C Storage

Abstract: Improving the productivity and genetic quality of local cattle, especially Ongole Cross Bred (known as PO) is applied through Artificial Insemination (AI). The success of AI must be supported by semen quality. Semen processing at 5°C can cause sperm membrane damage resulting in decreased semen quality, especially the viability of sperm. This results in reduced sperm fertility at the time of fertilization with the ovum. Viability is an important indicator for cold semen processing. The use of semen diluents, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Viabilitas adalah uji kualitas yang dilakukan untuk mengetahui persentase spermatozoa hidup atau mati setelah diberi perlakuan. Uji viabilitas untuk mengetahui spermatozoa hidup atau mati didasarkan pada perbedaan warna men gunakan pewaranaan eosin-negrosin [16]. Sperma tozoa hidup ditandai dengan spermatozoa tidak berwarna menandakan spermatozoa tidak menyerap pewarna dan spermatozoa tidak hidup ditandai dengan spermatozoa berwarna artinya spermatozoa menyerap warna.…”
Section: Pembahasanunclassified
“…Viabilitas adalah uji kualitas yang dilakukan untuk mengetahui persentase spermatozoa hidup atau mati setelah diberi perlakuan. Uji viabilitas untuk mengetahui spermatozoa hidup atau mati didasarkan pada perbedaan warna men gunakan pewaranaan eosin-negrosin [16]. Sperma tozoa hidup ditandai dengan spermatozoa tidak berwarna menandakan spermatozoa tidak menyerap pewarna dan spermatozoa tidak hidup ditandai dengan spermatozoa berwarna artinya spermatozoa menyerap warna.…”
Section: Pembahasanunclassified
“…According to Holden and Butter (2018), the availability of sexed semen would allow the selection of the best bulls and cows. In addition, 0.2% level of bovine serum albumin (BSA) could maintain the highest viability of sperm during eight days of storage (89.36±2.62%%) following Indonesian National Standards (Rachmawati et al, 2020). Furthermore, Rasad et al (2021) found that the quality of Etawah crossbreed sperm after sexing was affected by the BSA concentrations.…”
Section: Introductionmentioning
confidence: 99%